"WHY NOT SETTLE DOWN ALREADY?" A QUANTITATIVE ANALYSIS OF THE DELAY IN MARRIAGE. (28th April 2016) - Santos, Cezar; Weiss, David
Abstract : A striking change in American society in the last 40 years has been the decline and delay in marriage. The fraction of young adults who have never been married increased significantly between 1970 and 2000. Idiosyncratic labor income volatility also rose. We establish a quantitatively important link between these facts. If marriage involves consumption commitments, then a rise in income volatility delays marriage. We quantitatively assess this hypothesis vis‐à‐vis others in the literature. Increased volatility accounts for about 20% of the observed delay in marriage and is strong relative to other mechanisms.